Safety and effectiveness of tigecycline combination therapy in renal transplant patients with infection due to carbapenem-resistant gram-negative bacteria - Wang, Qin; Liao, Guiyi; Xia, Quan; Ge, Chaoliang; Ding, Handong (Frontiers in Cellular and Infection Microbiology, 2023)
Background Carbapenem-resistant gram-negative bacterial (CRGNB) infections are increasing among kidney transplant recipients, and effective therapeutic options are limited. This study aimed to investigate the efficacy and adverse events associated with combination therapy tigecycline in renal transplant patients with CRGNB infections. Methods This study retrospectively analyzed 40 Chinese patients with confirmed or suspected CRGNB infections who received tigecycline therapy. The patients’ case features and clinical and microbiological data were analyzed. Results A total of 40 renal transplant recipients received tigecycline therapy for a median duration of 9 (range, 3–25) days. CRGNB isolates were obtained from the organ preservation solution of the donor kidney in 28 patients, with confirmed transmission in 4 patients. Infections were detected in the bloodstream, urinary tract, sputum, and wound. The most prevalent isolates were Klebsiella pneumoniae (75%, 30/40), Acinetobacter baumannii (15%, 6/40), and Escherichia coli (10%, 4/40). A clinical response was observed in 32 (80%) patients. The 28-day all-cause mortality rate was 7.5% (3/40), while the one-year all-cause mortality rate was 2.5% (1/40). While one patient died owing to severe pancreatitis, no serious adverse events related to tigecycline therapy were reported. However, multiple indices of liver function and pancreatitis precursors increased after treatment with tigecycline compared to before treatment. Conclusion Tigecycline therapy appears to be well tolerated in renal transplant recipients with multidrug-resistant bacterial infections. Nevertheless, attention should be paid to adverse reactions related to tigecycline therapy, especially gastrointestinal reactions, and the related laboratory tests should be closely monitored.